Improving the Energy Performance of Buildings Learning from the European Union and Australia - Ries, Charles P. (RAND Corporation, 2009)
This study examines how policies to increase energy efficiency in buildings in the European Union and Australia have worked and draws implications for the design of similar public policies for the United States. It appears that effective policies to promote energy efficiency can be devised using information disclosure, building codes, financial incentives, and benchmarking. Insights are presented to help designers of analogous U.S. policies.